MANAGING PROJECTS IN A VIRTUAL ORGANISATION - Mills, Shaun (My University, 2011)
Owing to the constraints on traditional organisations, such as limited infrastructure and resources, companies are forming alliances and joint ventures in order to execute large, “fast track” projects, which they would not have been able to execute by themselves. These projects, which are managed as global virtual organisations, bring with them problems that are not found in the traditional project management organisation. The objective of this project was to perform a literature review to identify what problems are encountered by project management in these virtual organisations. A proposition was formulated containing the problematic factors identified. This proposition was than tested in a case study, involving qualitative analysis of interviews conducted, observation, and review of project documentation of an engineering organisation in South Africa that has managed projects on this basis. Analysis of the results confirmed the proposition that the problematic factors of communication, culture, language, technology, organisation structure, commitment, trust and planning manifest themselves during the execution of projects managed as virtual organisations. These results provided a basis for the development of a framework for management to use during the establishment of projects that are to be executed as virtual organisations. This framework can be used in order to reduce the risk of the problematic factors manifesting themselves
MBA - WBS
Keywords: Project management; Virtual organisations